Numerical investigation on cavitation in pressure relief valve for coal liquefaction. Issue 4 (15th January 2015) - Ou, G F; Li, W Z; Xiao, D H; Zheng, Z J; Dou, H S; Wang, C
Abstract: The pressure relief valve for regulating the level of the high-pressure separator works under a pressure difference up to 15 MPa in the temperature of 415 °C. Severe cavitation erosion and particle impact lead to the valve disc's mass loss. In this paper, three-dimensional turbulent cavitating flows in the pressure relief valve are numerically simulated to reveal the mechanism of mass loss at valve disc. The RNG k-ϵ turbulence model and the mixture model with a mass transfer for cavitation are employed to simulate the cavitating flow in the pressure relief valve. The result shows that there is phase change in the pressure relief process and cavitation bubbles would be transported by high-velocity backflow to the head of valve disc. For the local pressure higher than the saturated vapor pressure, the bubbles collapse at the head of disc and cavitation erosion is formed at the head of the disc. By comparing the cases of opening of 40%, 50%, and 60%, backflow velocity and cavitation region in front of the disc decrease with the opening increase. Therefore, during the actual operation, the pressure relief valve should be kept to a relatively large opening.